Redescrição de Platanichthys platana (Regan, 1917) (Clupeiformes, Clupeidae) com comentários sobre a distribuição geográfica. - Silva, Alessandra Barbosa da (2022)
A taxonomic and biogeographic review for the genus Platanichthys was necessary. In recent years, they have been identified as being of the species Platanichthys platana specimens collected in rivers and lakes of other hydrographic basins besides the then known ones. The species considered the smallest sardine in Brazil, always found in continental and coastal environments, including estuarine regions, began to be captured in waters of regions more in brazil, thus raising the hypothesis that these new specimens are a new species of the genus, until the monospecific moment. A total of 478 specimens identified as Platanichthys platana, from seven different hydrographic basins of South America (Baixo Paraíba do Sul, São João, Ribeira de Iguape, Alto Paraná, Guaíba, Atlântico Sul and La Plata), were analyzed. 40 morphometric analyses were performed, 21 non-overlapping (truss), and 13 additional morphological analyses. The differences observed between the analyzed populations didn’t support the hypothesis of being a new species for the genus Platanichthys, but after the analysis of all the material, it was possible to better determine its geographical distribution is to elaborate a better diagnosis for characterization and differentiation of the species in relation to other similar Clupeideos.